Pemanfaatan Kawasan Konservasi Perairan di Kota Pariaman - Ahmad Zikri; Roni Ekha Putera; Kusdarini Kusdarini (Pencerah, 2023)
The lack of knowledge and concern for the survival of turtles and the rampant trade and consumption of turtles, the steps that can be taken are to use conservation areas as ecotourism for visitors in the marine conservation area of Kota Pariaman which is carried out by the UPTD for conservation and supervision of marine and fishery resources. West Sumatera. This research was conducted using a qualitative description method. Data were collected through interviews with selected informants using purposive sampling technique, direct observation to see field conditions, and documentation by collecting documents related to regulations on the use of marine conservation areas. The theory used in this research is George C Edwards III which consists of several variables. The data obtained is then analyzed. The results showed that the implementation of the regulation of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia Number 47 / PERMEN-KP / 2016 concerning the use of water conservation areas in Pariaman City. First on the communication variable, that this policy is clear enough and well-transmitted and consistently implemented. Second, the resource variable for quantity is clearly lacking but in terms of quality it is good and adequate, for facilities it is adequate but there are some facilities that need to be updated. The three disposition variables for the appointment of bureaucrats have been effective, while incentives have been given as a form of motivation. The fourth variable for SOPs and fragmentation has been able to run well by policy implementers.